UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 70% RIMPANG KENCUR (Kaempferia galanga Linn) TERHADAP Streptococcus pyogenes SECARA In Vitro - Ratu Edo, Megaputri Yoriska; Pakan, Prisca Deviani; Rini, Desi Indria (Universitas Nusa Cendana, 2022)
Streptococcus pyogenes is a gram-positive bacterium that causes extensive infection, particularly in the respiratory tract and skin, also the 90% cause of pharyngitis cases encountered in the primary health care unit. Pharyngitis infections by S. pyogenes are treated with Penicillin G or other beta-lactam derivates, if left untreated or delayed may occur sekuele immunity, Acute Rheumatic Fever (ARF) that causes permanent damage to the heart valves or Rheumatic Heart Disease (RHD). Morbidity due to heart failure in RHD patient. In recent years there have been reports of resistance to antibiotic treatment in S. pyogenes infections cases. In East Nusa Tenggara, Kencur rhizomes (Kaempferia galanga Linn) is used for generations to cure complaints such as cough, flu, asthma, flatulence and abdominal pain. In accordance with previous research that proved Kencur rhizomes extract is an analgesic, anti-inflammatory, anti-helmintic, mosquito repellent, mosquito larvae growth inhibitor, vasodilator, anti-cancer, anti oxidant, sedative, anti-UVB and anti bacteria. The purpose of this research was to know the antibacterial activity of ethanol extract of kencur rhizome on S. pyogenes in vitro, effectiveness of Kencur rhizome extract as antibacterial and minimal concentration of Kencur rhizome extract which can inhibit the growth of S. pyogenes. The method of this research is True Experimental Research with Posttest Only Control Group Design as design. The sample of this study, used extract ethanol of Kencur rhizome which tested using the well diffusion method to observe the antibacterial activity prepare in eight concentrations (1 (100%), 2 (50%), 25%, 12.5%, 6.25%, 3.12%, 1, 56% and 0.78%), one positive control group (amoxicillin) and one negative control group (sterile aquadest) with three times replications. The results showed that the extract of ethanol Kencur rhizome has antibacterial activity but not effective as anti bacteria on the growth of S. pyogenes bacteria and the concentration 0.78% was determined as minimum inhibitory concentration.